Cation dynamics and growth morphology of aromatic rice under salt stress - Sultana, A; Baset Mia, MA; Ahmed, JU (Bangladesh Journal of Scientific and Industrial Research, 2021)
Salinity is an abiotic stress which affects plant’s growth, morphology and cellular functions, and alters the ionic balance in the cytosol and vacuole in various crops. In the present investigation, salt stress was tested with three rice (Oryza sativa L.) varieties/genotypes viz. Pokkali, Sunduri Samba, and Khasa with three levels of salinity (0, 6, and 9 dSm-1). In the investigation,growth, morphology, and ionic status in roots, stem, and leaf were observed under pot culture with three replicates in each treatment. The results of the experiment revealed that salt stress decreased in growth attributes namely, root dry matter, shoot dry matter, total dry matter and root: shoot ratio. Sunduri Samba showed higher values, but Khasa the lowest. Mineral ion content especially the cation in the plant tissue namely Na+, K+, Ca2+, Mg2+ differed significantly due to salt stress as well as the K+/ Na+ ratio decreased in root and shoot due to salinity. Sunduri Samba maintained quite higher K+/Na+ than the susceptible genotype. Due to salinity, different growth characteristics and K+ concentrations decreased but Na+ concentration increased. Here the tolerant genotype Sunduri Samba accumulated higher amounts of K+ than the susceptible genotype Khasa and altered the ionic ratios through distribution of Na+ ion in shoot. Bangladesh J. Sci. Ind. Res.56(3), 207-214, 2021